Classical and quantum phases in hexagonal boron nitride‐combined van der Waals heterostructures. Issue 3 (21st April 2020) - Zheng, Shoujun; Zhao, Mali; Sun, Linfeng; Yang, Heejun
Abstract: Since the discovery of graphene, two‐dimensional (2D) layered materials have attracted extensive attention owing to their unique properties and promising potential applications. In particular, van der Waals (vdW) heterostructures, artificially stacked with 2D materials, have provided an excellent platform to explore various applications and to unveil long‐standing mysteries in quantum and condensed matter physics. Here, we discuss recent progress in novel classical and quantum phases in vdW heterostructures, emerging through thickness‐dependent hexagonal boron nitride (h‐BN) combined with graphene and transitional metal dichalcogenides. As a cornerstone of vdW heterostructures, the h‐BN plays diverse roles, such as tunneling barriers, dielectric layers, clean substrates, and capping layers, to realize numerous intriguing devices: field‐effect transistors, tunneling light‐emitting diodes, resonant tunneling diodes, nonvolatile memories, Bose‐Einstein condensation, topological insulators, and graphene‐based superconductors. The vdW heterostructures with various roles of h‐BN continue to enrich our knowledge for quantum physics and practical future device applications. Abstract : Various van der Waals heterostructures with hexagonal boron nitride (h‐BN) are categorized by the thickness of the h‐BN and intriguing applications with classical and quantum phases toward resonant tunneling devices, nonvolatile memories, Bose‐Einstein condensation, and moiré pattern‐induced superconductivity and excitons are explored.